Sierra Leone : : Rice growing scheme - Great Britain Colonial Office; National Archives (Great Britain); Adam Matthew Digital (Adam Matthew Digital, 1933)
Typescript and ms. memoranda recording Colonial Office decisions in relation to a scheme to establish and promote rice growing and milling in Sierra Leone